The Effect Of Combination Of Octadecanoic Acid, Methyl Ester And Ribavirin Against Measles Virus - Reagan Entigu, Linton @ Jerah; Samuel, Lihan; Ismail, Ahmad (International Journal Of Scientific & Technology Research, 2013)
Ribavirin is a broad spectrum antiviral drug and has been used to treat various diseases. It has been used as a treatment for subacute sclerosis panencephalitis (SSPE) caused by measles virus infection. However, there were several adverse effects when receiving ribavirin treatment. Other than ribavirin and vaccine, there is no cure for the disease thus medicinal plants being studied for their potential active compounds to be used as either mono or combined treatment with drugs. The objective of this study was to test antiviral activity of octadecanoic acid, methyl ester (OA), extracted from Cymbopogon nardus (sweet lemon grass) against measles virus in both mono and combination with ribavirin. The cytotoxicity and antiviral activity were tested at low concentration for the compound (25, 12.5 and 2.5 μg/ml) and ribavirin (0.1, 0.05 and 0.01 CC50). The cytotoxicity result showed that the low concentrations of both compounds have low cytotoxicity on Vero cell although there was slight increment of toxicity when they were combined. However, the combined treatment showed higher antiviral activity (p <0.05) compared to single treatment of both compounds (OA12.5 μg/ml + RBV0.05CC50: 94.38 ± 1.5%, OA12.5 μg/ml: 67.09 ± 0.2%, RBV0.05CC50: 51.12 ± 2.1%). The result has also shown that decreasing of the concentration of the combination could still maintained the antiviral activity comparable to single treatment and less cytotoxicity toward Vero cell. This study has proven that OA can be combined with commercial drug such as ribavirin to produce higher antiviral activity at lower concentration for combination of both compounds.